3D 프린터 기반의 여성용 맞춤형 중창 디자인을 위한 모델링 프로세스 제안 - 235-240mm의 20대 여성을 대상으로 - 김정현; Kim Jeong-hyeon; 정의철; Jung Eui-chul (한국디자인포럼, 2015)
본 연구의 목적은 3D프린터 기반의 맞춤형 중창 디자인을 위한, 중창 디자인 요소를 정의하고 모델링 프로세스를 제안하는 데에 있다. 연구의 목적을 달성하기 위해 맞춤형 중창 디자인 시 필요한 발 치수 요소를 선정하였고 최적화 사이즈를 도출하여 모델링 하였다. 또한 3D프린터로 출력하여 착화감 테스트를 진행하였다. 중창 디자인에 필요한 발 치수 요소로는 발길이와 발너비, 발아치(Arch)이다. 최적화 사이즈는 사용자의 발길이, 발너비를 바탕으로 길이를 가감하여 도출 하였다. 발길이를 기준으로는 발의 양끝에 간격을 주었고, 발너비에 대해서는 감산하여 모델링 하였다. 착화감을 높이기 위해 발모양에 대한 고려가 중요하여, 발의 내·외측면을 사진으로 찍어 발아치(Arch)모양을 모델링 프로세스에 반영하였다. 제안한 프로세스의 타당성 평가를 위하여, 3D프린터로 중창을 출력 하고 피험자들에게 착용하게 하여 사용성 평가를 진행하였다. 피험자는 한국 여성 표준 발 크기인 235~240mm를 착용하는 20대 여성 3명을 단순 무작위 추출을 통해 정하였으며, 제작한 중창에 올라서게 하여 최대 족저압력과 평균 족저압력을 측정하였다. 왼발을 기준으로 측정한 결과, 최대 족저압력의 최대치는 후족부에서 발생하였으며, 후족부 압력의 최대치가 실험자가 평소에 사용하는 일반 중창과 비교하여 다소 낮게 나타났다. 이는 제안한 모델링 프로세스를 활용하면 맞춤형 중창이 한 곳에 집중된 압력을 분산시켜 최대 족저압력을 감소시킬 수 있다는 것을 의미한다. 본 연구는 향후 맞춤형 신발 제작을 위한 기초 연구로 활용될 수 있을 것이다. This research aimed to propose modeling process development for customized woman midsole design based-on 3D Printing technology. To accomplish the objective, we suggested design factors of customized midsole, and presented the optimized foot size, process of midsole modeling. Also, using 3D printed midsole, we performed fit test. Necessary design factors of customized midsole were foot length, ball width and foot arch. Optimized foot size was derived by adding and subtracting based on foot length, ball width. we gave a spare space from end of foot length and subtracted the 6% on ball width. For increasing the comfort of midsole, we took a picture with inner/outer foot side surface and applied to modeling. In order to evaluate the validity of suggested process, we printed a midsole using 3D printer, and conducted usability test to the subjects. The subjects are three women in their 20s, who are wearing a Korean female average foot size of 235~240mm by using the simple random sampling method. Then, subjects stood on the customized midsole and we measured the peak and average plantar pressure, based on the left foot. As a result, the maximum value of peak pressure found on the heel regions. And the peak pressure of heel regions was slightly lower compared to subject`s normal midsole. This result showed that suggested customized midsole modeling process can reduce the high plantar pressure on the heel regions by redistributing the pressure. This finding can be used as a basis for further research of customized shoes making.